Mid-Term Clinical and Radiological Outcomes of Lateral Meniscal Allograft Transplantation with Suture-Only Fixation Plus Capsulodesis - Morales-Avalos, Rodolfo; Masferrer-Pino, Ángel; Padilla-Medina, José Ramón; Amestoy-Ramos, Jorge; Ibáñez, Maximiliano; Perelli, Simone; Ariztegui-Andrade, Cristina; Espregueira-Mendes, João; Monllau, Joan Carles (The Journal of Knee Surgery, 2023)
Meniscal allograft transplantation (MAT) is an effective reconstructive procedure for treating a symptomatic postmeniscectomy syndrome. It consists of replacing the lost meniscal tissue aiming to improve the clinical outcomes and prevent progressive deterioration of the joint. The aim of this study was to evaluate meniscal graft survivorship and report on the radiographic (in terms of graft extrusion and joint space width and alignment) and the functional results through a midterm follow-up of lateral MAT performed with a soft tissue fixation technique after capsulodesis. In total, 23 patients who underwent lateral MAT as a single procedure were included. The Knee injury and Osteoarthritis Outcome Score, Lysholm, Tegner, and visual analog scale scales were used for patient assessment. Magnetic resonance imaging and a complete radiographic protocol were conducted to determine the degree of meniscal extrusion and the changes in the degree of osteoarthritis and coronal alignment. Assessments were performed after 2 and 7 years of follow-up. A significant improvement in all the scores, relative to preoperative values, was found after 7 years of follow-up. This improvement remained consistent throughout the first and second follow-up periods. A mean absolute extrusion of 2.2 mm ± 1.6 and an extrusion percentage of 28.0% ± 11.43 were found, with no significant differences throughout the follow-up periods. There was no statistically significant difference in terms of the frontal mechanical axis and joint space narrowing between the preoperative value and at the first and second follow-up periods. A survival rate of 85.7% was found after 7 years of follow-up. Capsulodesis results in a low degree of meniscal extrusion in isolated lateral MAT fixed with a suture-only technique, which is maintained after 7 years of follow-up, with a high graft survival index (>85%) and satisfactory results on the functional scales.
Keywords: capsular fixation; capsulodesis; lateral meniscus; meniscal extrusion; meniscal; transplantation